INSÄN KÄMIL , ANTARA MITOS DAN REALITAS - Danusiri, Danusiri (TEOLOGIA, 2014)
Abstract: Islam as a religion delivered by Muhammad saw. bin Abdullah (w.632) is based on the revelations he received from God. At the end of his age, the religion is stated as a perfect religion because it contains a description of all aspects of life (tibyanan likulli syai). To become the most religionist in Islam, every Moslem should follow the religious way he was because he is a good example (uswatun hasanah), especially the religious rituals dimension. The implication is clear that looking for other models of religious practices except him are certainly would not be the best because there is no guarantee of truth. Over time, many factors occur in the dynamics of the history of Moslem. The values of Islam built by the Messenger have changed a lot in the society. Muhammad position as the top model has shifted into the lower one. The concept of insÄn kÄmil Â (perfect man) pops out then. They are also the loyal followers of the Messenger of Allah, introducing the idea of speculative-philosophical-mystical religious rituals and a very extreme and radical practice of religious rituals if measured from his norm and religious practices. Nevertheless, the mass movement of Moslem under the shadow of the perfect man considered as something between a myth and reality refer to the texts of the Quran and al-sunnah. Abstrak: Islam sebagai agama disampaikankan oleh Muhammad saw. bin Abdullah (w.632) atas dasar wahyu yang ia terima dari Tuhan. Pada usia akhir-akhir hayatnya, agama ini dinyatakan sebagai agama yang sempurna karena memang mengandung penjelasan semua aspek kehidupan (tibyanan likulli syaiâ). Untuk menjadi agamawan yang paling baik di dalam Islam, setiap muslim supaya mengikuti cara ia beragama karena ia adalah contoh yang baik (uswatun hasanah), khususnya dimensi ritual keagamaan. Implikasinya mencari model praktik-praktik keberagamaan selain beliau tentu tidak akan menjadi yang paling baik karena tidak ada jaminan kebenarannya. Seiring perjalanan waktu, banyak faktor terjadi dalam dinamika sejarah umat Islam. Nilai-nilai yang dibangun oleh pembawa Islam pun banyak yang berubah. Posisi Muhammad saw. sebagai top model dalam beragama tergeser pada peringkat yang lebih rendah. Konsep insÄn kÄmil Â bermunculan. Mereka yang juga âpengikut setiaâ Rasulullah, memperÂkenalkan gagasan spekulatif-filosofis-mitis dan praktik ritual keagamaan yang sangat eksÂtrim dan radikal jika diukur dari norma dan praktik keberagamaan beliau. Meskipun demikian, gerakan massal umat Islam di bawah bayang-bayang insÄn kÄmil Â yang jika ditimbang dengan neraca teks-teks al-Quran maupun al-sunnah dapat dinyatakan sebagai sesuatu antara mitos atau realitas. Keywords: uswatun hasanah, penggeseran nilai, insÄn kÄmil, Â praktik keberagamaan, mitos.